A review of MOFs and its derivatives for lithium ion battery anodes. Issue 1 (February 2021) - Chen, Weichen; Liu, Sen; Shen, Jialin
Abstract: With the development of electric vehicles and clean energy, the demand for lithium-ion batteries (LIBs) has increased significantly in recent decades. As traditional anode materials can only basically meet the requirements of current consumer electronics products, metal-organic framework (MOFs) material and its derivatives attract great attention to become a potential substitute with advanced performance. Pristine MOFs material has greater development potential in terms of high energy density anode. MOFs-derived materials, including porous carbon material, metal oxide and composite material, could exhibit improved electrochemical behaviours and better stability. This article introduces the pristine MOFs and MOFs-derived materials as an anode in lithium-ion batteries, as well as their modification methods that have been widely studied at the current stage. In the end, we discussed the future development trends of various MOFs materials.